2021
DOI: 10.7759/cureus.15947
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hearing Screening: Prevalence of Unilateral and Bilateral Hearing Loss and Associated Risk Factors

Abstract: Introduction: Newborn hearing screening is essential for early identification of hearing loss to decrease the adverse effects of hearing loss. The objective of this study was to determine the prevalence of hearing loss and risk factors of congenital hearing loss in newborns.Methods: In this analytical case-control study, a hearing screening test was performed for all newborns aged 3-14 days.Results: Of 5,500 newborns evaluated, 24 newborns had hearing loss. The prevalence of hearing loss was 4.36 per 1,000. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…The finding that the referral rate for hearing screening was lower for females than for males in the 2 years studied was consistent with results reported by Yan et There were no significant differences in referral rates after the results of genetic and hearing screening were stratified by prematurity, suggesting that there may not necessarily be an association between prematurity and positivity in genetic screening for deafness. Sabbagh et al reported that the main risk factors for hearing loss included a low gestational age (<35 weeks) (41). In the current study, preterm delivery was defined as less than 37 weeks of gestation.…”
Section: Association Between Sex and Gestational Age And Hearing Lossmentioning
confidence: 79%
“…The finding that the referral rate for hearing screening was lower for females than for males in the 2 years studied was consistent with results reported by Yan et There were no significant differences in referral rates after the results of genetic and hearing screening were stratified by prematurity, suggesting that there may not necessarily be an association between prematurity and positivity in genetic screening for deafness. Sabbagh et al reported that the main risk factors for hearing loss included a low gestational age (<35 weeks) (41). In the current study, preterm delivery was defined as less than 37 weeks of gestation.…”
Section: Association Between Sex and Gestational Age And Hearing Lossmentioning
confidence: 79%
“…12 In this study the prevalence of bilateral refer DPOAE during the first test on day 2 among GDM, preeclampsia and control group was 15.81%, 19.52%, and 3.52% respectively which is high compared to other studies. 13 However the prevalence reduced drastically at the second DPOAE test among GDM, preeclampsia, control group that is, 4.5%, 3.33%, and 0.58% respectively. Subsequent ABR also showed Pass result in most of the neonates who had failed repeat DPOAE indicating that the hearing loss is transient which is consistent with previous studies by Alan and Alan.…”
Section: Discussionmentioning
confidence: 90%
“…The findings indicated that the probability of passing results in newborns without NICU admission was two times greater than in those with NICU admission. Other studies also found that NICU hospitalization for more than 5 days could be a risk factor for hearing loss [24][25][26]. Hearing loss caused by staying in NICU could be due to mechanical ventilation for asphyxia and respiratory distress of newborns in the NICU that adversely damages the peripheral auditory system function [2,26].…”
Section: Total Resultsmentioning
confidence: 99%